Automotive Center Di Pekanbaru Dengan Pendekatan Arsitektur High Tech - Prabowo, Jevri; Faisal, Gun; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Automotive center is a central that can accommodate all activities consumer, manufacturer or seller related to automotive of the car. Pekanbaru as the capital of Riau Province has a number of four-wheeled vehicles that continue to increase annually, so that the automotive market is potentially growing. Pekanbaru City does not have a special automotive center building, the current condition of companies related to automotive is still scattered. Pekanbaru Automotive Center planning becomes the solution of the problem that serves as an educational, commercial and social facilities and there are supporting facilities for user activities. This method uses High Tech Architecture because being able to present building functions as a place with automotive image representing a technology, manufacturing, sophisticated, flexible and functional. The concept used is “Piston” that take the characteristic of the piston motion system, to make it more flexible in the construction process or to give the engine resemble quality. Keyword : Automotive Center, Pekanbaru, High Tech Architecture, Piston